English language teaching textbooks in Nicaragua. A study of the cultural content in Secondary English Book - 7th grade - Malespín García, Alvaro Javier, | Moreno Rodríguez, Handel Osmar | Tórrez Zamora, Nahúm Misael Tórrez Zamora Nahúm Misael (Nicaragua | ESTELI UNAN-Managua, FAREM-Estelí, Nicaragua, 2019)
Textbooks are the primary resources used in many classrooms around the world, since; they convey knowledge and information to students in an easy and organized way.; Scholars define the textbook as a resource for presenting materials and a source aimed; for learners to practice and complete the activities in order to develop their language; skills. Textbooks are also expected to provide students with useful knowledge of the; world and their own culture. The first series of English textbooks created by the; Nicaraguan Ministry of Education (MINED) was made available in 2016. This paper; analyzes the cultural content present in these textbooks and whether they offer enough; and relevant content about the world and the students' local culture. A brief discussion is; included to determine the extent to which this series of textbooks familiarize learners with; their culture and traditions while at the same time helping them to become proficient in; the English language. Finally, this paper aims to investing at whether textbooks and their; content are relevant, as perceived by a group of teachers from Esteli.
Seminario-(Licenciado en Ingles)-Universidad Nacional Autónoma de Nicaragua SM EIN 378.242 Mal 2018
Keywords: Enseñanza Aprendizaje, | Cultura-Enseñanza, | Inglés-Enseñanza, | Inglés-Libro de texto, | Inglés-Seminario-2018